Trustworthiness of Inbound Tourists’ on social media platforms towards destination choice - Dogra, Jeet (Turizam, 2020)
Given the relative proliferation of social media users and the significance of Information collection in a consumer’s decision journey, this study tried to identify the most widely and frequently used platforms for India’s travel information. In order to evaluate the trustworthiness of inbound tourists on social media platforms, focus group interviews were conducted across 12 Indian states in which 300 foreign tourists from 86 countries took part. Tripadvisor and Facebook were the two social media platforms with the most number of users seeking India’s travel information. The findings of the study conclude the use of multiple social media platforms for varied information and destination choice.